An Automated Approach to Describing Fiction: A Methodology to Use Book Reviews to Identify Affect. Issue 8 (12th October 2021) - Moulaison-Sandy, Heather; Adkins, Denice; Bossaller, Jenny; Cho, Hyerim
Abstract: Subject headings and genre terms are notoriously difficult to apply, yet are important for fiction. The current project functions as a proof of concept, using a text-mining methodology to identify affective information (emotion and tone) about fiction titles from professional book reviews as a potential first step in automating the subject analysis process. Findings are presented and discussed, comparing results to the range of aboutness and isness information in library cataloging records. The methodology is likewise presented, and how future work might expand on the current project to enhance catalog records through text-mining is explored.